Mapping Twitter’s Information Sphere In The Lead-Up To The Brexit Referendum: How Eurosceptic Views Outpaced Their Rivals - Hänska, Max; Bauchowitz, Stefan (AoIR Selected Papers of Internet Research, 2017)
How did Eurosceptic (Leave) and pro-European (Remain) activity compare on social media in the run-up to the EU referendum, what kind of information did users share, and did this confine the two camps to informational echo chambers? To answer these questions we collected more than 7.5 million Brexit-related tweets through Twitter’s streaming API. We enriched our data using a support vector machine to identify which tweets clearly supported the Leave or Remain camp, mapped twitter users within our data to the location specified in their user profile, and mined URLs shared in tweets. We find that Leave users were more numerous, and individually more active in tweeting to support their cause. Leave users also tended to be less open, and more engaged within their own echo-chamber, something that is reflected in the URLs they shared. URLs pointing to Eurosceptic domains were shared more widely than those pointing to pro-European domains. Surprisingly, The Express was one of the most prominent domains shared on twitter, more than its more prominent Eurosceptic counterpart, the Daily Mail. Overall, twitter users who supported Leave appeared to be much more active and motivated in advancing their cause than Remainers were in advocating continued EU membership. The use of twitter in the Brexit campaign demonstrates how social media users pushed a hitherto marginal political agenda to the front and center of public discourse.